How entrepreneurial characteristics influence company creation: a cross-national study of 22 countries tested with panel data methodology - Álvarez-Herranz, Agustín; Valencia-De-Lara, Pilar; Martínez-Ruiz, María Pilar (Journal of Business Economics and Management, 2011)
This study analyzes, from a multicountry perspective, the influence of the sociodemographic profiles of nascent and new entrepreneurs on their behavior. The panel data-based research approach combines temporal series and cross-sectional data to assess entrepreneurial activities across 22 countries with varying income levels. The results show that entrepreneurs’ characteristics influence entrepreneurial behavior significantly and positively, in the following order: previous experience of the founder, age, and education. These findings suggest valid recommendations for stimulating entrepreneurship, both for enterprising business founders and for the institutions responsible for designing economic and regional development policies. Article in English. Verslumo charakteristikų įtaka įmonės kūrimui: studijos, atliktos 22 valstybėse, rezultatų pristatymas Santrauka. Straipsnyje pristatomų tyrimų rezultatai apima sociodemografinių veiksnių įtakos naujai kuriamam verslui ir jo aplinkai analizę. Tyrimas buvo atliktas 22 valstybėse. Jo rezultatai rodo, kad tam tikros individualios asmens verslumo savybės turi teigiamą įtaką paties verslo organizavimui, pavyzdžiui, ankstesnė verslininko patirtis, amžius ir išsilavinimas. Straipsnio autoriai pateikia rekomendacijas, susijusias su verslumo skatinimu, jos turės įtakos ne tik ekonominei, bet ir regioninei vystymosi politikai. Reikšminiai žodžiai: verslumas, sociodemografinės charakteristikos, elgesys, metodologija.